The Effect of Business Model on Financial Performance of Banking Companies in ASEAN and MENA - Yulia Astuti, Niken; Nazir Ahmad, Gatot; Warokka, Ari (Lafadz Jaya Publisher, 2024)
This research is expected to determine the influence of business models on financial performance as measured by market power. This research involves conventional banking in the ASEAN and MENA regions which have available data for the period 2010 to 2019 to avoid the influence of the Global Financial Crisis and the Covid 19 Pandemic. This research uses Panel Data analysis techniques, which is a combination of time series data and cross section data. In measuring banking competition, researchers use the Lerner Index. The Lerner Index is an indicator of the level of market power that holds a strong position in measuring banking competition, the higher the Lerner Index value, the greater the bank's power in controlling the market, resulting in lower levels of banking competition. The results of this research indicate that there is a positive influence between the Business Model and Market Power both in the ASEAN region and in the MENA region. This suggests that choosing the right business model can generate sustainable competitive advantages and higher financial performance for banks that adopt it.